Impact Management Strategies in the Development of the National Capital on Local Communities - Prabowo, Tri Bagus; Wiratama, Dias Oldy (Arbain Publishing, 2025)
One of the main problems is the non-involvement and neglect of communities in the new capital planning and development process. The research method used in this research is a qualitative descriptive analysis technique. This approach was chosen because it allows researchers to understand in depth the impact and risks of moving the country’s capital on the Indonesian economy. In this case, policy alignment between the central government, regional government and other related actors is crucial to ensure the success of the development of the new capital city and the welfare of the people living around it. At the same time, it should also be noted that the development of the nation's capital can have negative impacts. By carefully evaluating policies, we can find out whether the development of the nation’s capital will have a positive impact or even cause problems for the surrounding community. it is also necessary to pay attention to community participation and involvement in the development process of the nation's capital so that their interests and needs can be properly accommodated.